Micropropagation Of Serpgandha (Rauvolfia Serpentina L. Benth): An Endangered Medicinal Plant (Applied Biological Research, 2014)
An efficient protocol for propagation of Rauvolfia serpentina through in  vitro culture was standardized. Of the various combinations of phyto hormones evaluated, 0.5 mg L-1indole acetic acid (IAA) +0.5 mg L-1 benzyl amino purine (BAP) + 1.0 mg L-1kinetin highly favoured callus  induction (32.8%). High callus-mediated shoot regeneration was seen on  MS medium supplemented with 1.0 mg L-1IAA + 0.5 mgL-1BAP + 0.5 mg L-1kinetin. Low auxin (IAA, 0.5 mg L-1) with higher concentration of cytokinin (0.5 mgL-1BAP +1.0mg L-1kinetin) gave higher shoots culture-1 (6.6) with mean shoot length of 3.2 cm. In direct shoot regeneration, best  growth of axillary shoots was achieved in MS medium supplemented with0.2 mg L-1IAA + 0.2 mg L-1 BAP + 0.2 mg L-1kinetin with maximum  shoots culture-1(10.0) and shoot length (4.4 cm). The root induction was  highest (84.3%) in MS medium supplemented with IBA (0.5 mg L-1).  The rooted plantlets were successfully established in field.
Keywords: Endangered species; in vitro propagation; medicinal plant; Rauvolfia serpentine